SOCIAL CORPORATE IMPLEMENTATION RESPONSIBILITY PT. INDOCEMENT IN ISLAMIC ECONOMIC PERSPECTIVE - Sutono (Journal of Social Science, 2020)
This research is about "Implementation of PTIndocement's Corporate Social Responsibility in thePerspective of Islamic Economy". The problem is based onthe community who are still having difficulty in gettinginformation about PT Indocement's CSR programs. Thisstudy uses qualitative research, the data sources used aretheoretical and empirical, theoretical data are data derivedfrom manual books that are related to the title of this study.The purpose of this study is to find out how the applicationand what factors are obstacles and how the completion ofCSR PT Indocement. The implementation of PTIndocement's corporate social responsibility in the village ofWest Palimanan still faces several obstacles. Such as thelack of ongoing monitoring, evaluation and motivation to thefostered partners. And the lack of transparency and outreachwith the West Palimanan village government. The factorsthat become obstacles are. Such as the problem in providinginformation to the people who are PT Indocement's CSRguided areas, the lack of communication to the WestPalimanan village government. In terms of channelinginformation to the community PT Indocement must beincreased from all stakeholders. Like the local villagegovernment, organizations and academics to maintain goodcommunication. So that if this happens surely theinformation provided by the company will be conveyed bythe people of West Palimanan Village.Key words: Corporate Social Responsibility, PTIndocement, West Palimanan